The stationary G/G/s queue with non-identical servers. (1998) - Gall, Pierre Le
Abstract : We extend a recently developed factorization method to the case of the G / G / s queue with non-identical servers, by presenting three simple properties which lead to a simple numerical calculation method. We compare our results with those determined by classical Markovian (phase) methods in the case of the symmetrical M / G / s queue, and for the mean queueing delay we compare with results given by traffic simulation.